An adaptive integration method for hybrid-dimensional simulations of aeroengine flight statuses by incorporating computational fluid dynamics models of turbomachinery subcomponents - Weimin Deng; Xiting Wang; Yibing Xu; Haoyang Xu (Engineering Applications of Computational Fluid Mechanics)
Hybrid-dimensional simulations can balance simulation accuracy and computational costs. However, applying hybrid-dimensional simulations to flight status remains challenging due to weak convergence. In this study, an adaptive integration method for hybrid-dimensional simulations was developed by introducing both adaptive incorporation schemes and polynomial transformations into the existing direct integration method. Experimental validations and T-MATS analysis show that errors in the thrust and specific fuel consumption of throttle characteristics are within 2% and 3%, respectively. Hybrid-dimensional simulations using both adaptive and existing direct integration methods were then applied to predict flight speed and altitude characteristics. Overall, the adaptive integration method demonstrates a broad convergence range for altitude (0-10 km) and speed (0-0.9 Ma) characteristics, requiring 25 iteration steps with co-working errors of less than 10−03. However, the direct integration method covers smaller ranges for altitude (0-1 km) and speed (0-0.4 Ma) characteristics, requiring 50 iteration steps with co-working errors of larger than 10−03. The results indicate that hybrid-dimensional simulations using the adaptive integration method exhibit good stability and convergence in the flight status compared to the direct integration method. Moreover, both the speed and altitude characteristics using the adaptive integration method cost approximately 24 hours on a computer workstation.